2005
DOI: 10.1103/physreve.71.041102
|View full text |Cite
|
Sign up to set email alerts
|

Two approaches toward a high-efficiency flashing ratchet

Abstract: For a flashing ratchet with periodic potentials fluctuating via random shifts of one-half period, a high efficiency is shown to result from two mechanisms. The previously reported one [Yu. A. Makhnovskii, Phys. Rev. E 69, 021102 (2004); V. M. Rozenbaum, JETP Lett. 79, 388 (2004)] is realized in the near-equilibrium region and implies, first, the presence of a high barrier V0 blocking the reverse movement of a Brownian particle and, second, identical, though energy-shifted, portions of the asymmetric flat poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The power output, as usual, reads P out = F A. The power input in this case is found to be [17][18][19]…”
Section: Energetic Efficiencymentioning
confidence: 67%
See 2 more Smart Citations
“…The power output, as usual, reads P out = F A. The power input in this case is found to be [17][18][19]…”
Section: Energetic Efficiencymentioning
confidence: 67%
“…A more detailed and rigorous consideration of efficient flashing ratchets is presented in Refs. [18][19][20], where it is shown that the deviation of the maximum efficiency from unity decays exponentially with increasing V 0 at the instantaneous switching of the potential profiles and decays much slower (according to a power law at large V 0 ) when this switching occurs for a finite time interval.…”
Section: Energetic Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we identify two parameters, the shape of the potential and the amount of friction on the electron (defined as the ratio of the potential oscillation timescale to the electron relaxation timescale), that, when explored simultaneously over a large parameter space, reveal two modes of ratchet operation that produce current by two different mechanisms. Prior work that explored the effect of shape on the behavior of the ratchet current focused on variations to a single potential [28][29][30][31][32][33][34]; however, while the current from a ratchet of a single shape does show resonances at certain oscillation frequencies [20], examining the frequency dependence of a single shape does not make apparent the transition from under-damped to over-damped ratcheting mechanisms. Identifying this transition, which is only possible when considering the complete space of biharmonic shapes and a large range of friction values, is critical in uncovering physically intuitive behaviors, and relating these behaviors to structural features of this complex system.…”
Section: Introductionmentioning
confidence: 99%
“…Much promise is shown by the high‐efficiency types of Brownian motors such as the model with the potential fluctuating by half a period and the so‐called catalytic wheel acting as a molecular pump. Highly efficient conversion of energy input into mechanical energy output in these models is attributed to (i) a high and narrow barrier blocking the reverse motion and (ii) the identical but mutually energy‐shifted potential reliefs on both half‐periods 6, 23–26. Particle transport through biological membranes driven by electric‐field fluctuations is described by the “catalytic wheel” model 26.…”
Section: Resultsmentioning
confidence: 99%